The Role of Immune Microenvironment in Maxillofacial Bone Homeostasis - Na Li; Na Li; Lin Fu; Lin Fu; Zehan Li; Zehan Li; Yue Ke; Yue Ke; Yanqiu Wang; Yanqiu Wang; Jintao Wu; Jintao Wu; et al. (Frontiers Media S.A., 2021)
Maxillofacial bone defects are common medical problems caused by congenital defects, necrosis, trauma, tumor, inflammation, and fractures non-union. Maxillofacial bone defects often need bone graft, which has many difficulties, such as limited autogenous bone supply and donor site morbidity. Bone tissue engineering is a promising strategy to overcome the above-mentioned problems. Osteoimmunology is the inter-discipline that focuses on the relationship between the skeletal and immune systems. The immune microenvironment plays a crucial role in bone healing, tissue repair and regeneration in maxillofacial region. Recent studies have revealed the vital role of immune microenvironment and bone homeostasis. In this study, we analyzed the complex interaction between immune microenvironment and bone regeneration process in oral and maxillofacial region, which will be important to improve the clinical outcome of the bone injury treatment.